2022
DOI: 10.1155/2022/3997947
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electroacupuncture on Short-Chain Fatty Acids in Peripheral Blood after Middle Cerebral Artery Occlusion/Reperfusion in Rats Based on Gas Chromatography–Mass Spectrometry

Abstract: Previous fundamental and clinical research has shown that electroacupuncture (EA) at the acupoints of Quchi (LI11) and Zusanli (ST36) can successfully alleviate motor dysfunction following stroke. Additionally, it has been discovered that gut microbiota and their metabolites play an essential role in stroke. However, the relationship between the metabolites of gut microbiota and the efficacy of EA is still unclear. Therefore, the aim of this study was to evaluate the mechanism of EA at LI11 and ST36 in the tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…Relevant studies have shown that acupuncture has a positive effect on the treatment of ischemic stroke through the interaction between the gut microbiota and the immune response; it can correct disorders in intestinal microbiota, reduce the immune inflammatory response, and promote the recovery of brain tissue damage and neurological function after stroke (51, 52). Acupuncture at LI11, GB34 and ST36 promotes recovery after stroke by regulating intestinal microecology and plasma metabolism (53). Acupuncture at GV20 and ST36 can benignly modulate gut microbiota dysbiosis and significantly reduce intestinal inflammation (54).…”
Section: Discussionmentioning
confidence: 99%
“…Relevant studies have shown that acupuncture has a positive effect on the treatment of ischemic stroke through the interaction between the gut microbiota and the immune response; it can correct disorders in intestinal microbiota, reduce the immune inflammatory response, and promote the recovery of brain tissue damage and neurological function after stroke (51, 52). Acupuncture at LI11, GB34 and ST36 promotes recovery after stroke by regulating intestinal microecology and plasma metabolism (53). Acupuncture at GV20 and ST36 can benignly modulate gut microbiota dysbiosis and significantly reduce intestinal inflammation (54).…”
Section: Discussionmentioning
confidence: 99%
“…The Modified Neurological Severity Scores (mNSS) was used for analysis ( Ke et al, 2022 ). The mice were scored on the first, third and fifth days of modeling to observe the neurological deficit of mice in each group, including exercise test, sensory test, balance test, reflex test and abnormal exercise.…”
Section: Methodsmentioning
confidence: 99%
“…Probiotics can also improve the negative emotions of IS patients, including anxiety and depression, 3 months after stroke (Bailey and Cryan, 2017;Liu et al, 2020). Probiotic treatment not only alters the microenvironment to limit pathological progress but also plays a complementary role by promoting the pharmaceutical management of calciumchannel blockers and statins (Liu W. et al, 2022). Combinatorial therapy with regenerative medicine, such as stem cell therapy, has also been found by some researchers to increase the level of the neurotrophic factor brain-derived neurotrophic factor (BDNF) through symbiotic treatment to enhance neurogenesis and poststroke cognitive function.…”
Section: Probiotics and Prebiotics In Ismentioning
confidence: 99%
“…Angong Niuhuang Pill (Zhang H. et al, 2022) the family Prevotellaceae, the genus Alloprevotella, the phylum Bacteroidota↓ the family Lachnospiraceae, the genera Lachnoclostridium, the phylum Firmicutes, Enterorhabdus, Colidextribacter, Roseburia, Lachnospiraceae_UCG-006↑ prostaglandin I2 and uridine↑ Buyang Huanwu decoction (Liu W. et al, 2022) Lactobacilli, Bifidobacteria↑ Escherichia coli, Actinobacterium↓…”
Section: Tcm Prescriptionmentioning
confidence: 99%
See 1 more Smart Citation